Selection of Yeast Strains for Ethanol Fermentation of Glucose-FructoseSucrose Mixture - J. Jasman; Irfan Dwidya Prijambada; Chusnul Hidayat; Donny Widianto (Indonesian Journal of Biotechnology, 2012)
This study was aimed to compare the ability of some yeast strains to consume sugars (sucrose, glucoseand fructose) and to convert them into ethanol during fermentation. The results of this comparison will be thebasis of considerations in choosing the right strain to be used as a mixed culture to increase the productionof ethanol from substrate containing a mixture of sucrose, glucose and fructose, such as juice of cane andsweet sorghum. The study was conducted using fermentation in substrate consisting of glucose, fructose,and sucrose separately, glucose-fructose mixture, and glucose-fructose-sucrose mixture using some yeaststrains: FNCC3012, OUT7009, OUT7027, OUT7055, OUT7080, OUT7096, OUT7903, OUT7913, and OUT7921.Following the fermentation, analysis of the produced ethanol and the remaining sugar was conducted. Theresults of study indicated that the strains with the highest substrate consumption were OUT7921, OUT7096,OUT7055, OUT7027, and OUT7913 for glucose, fructose, glucose-fructose mixture, sucrose, and glucosefructose-sucrose mixture, respectively. Strains that produced highest concentration ethanol were OUT7096 inglucose and sucrose substrates, OUT7921 in substrate of glucose-fructose mixture and sucrose, OUT7913 insubstrate of glucose-fructose-sucrose mixture. Upon consideration of each strain capacity, both in consumingsugar and producing ethanol, the recommended strains for use in mixed culture in bioethanol fermentationusing mixed substrate of glucose, fructose and sucrose are OUT7096, OUT7913, and OUT7921.